Analisis Perawatan Cutter Section Dredger Dengan Metode FMEA dan OEE - Hardiatama, Intan; Yudah, Norman Audi Erlangga Pradipta; Sidartawan, Robertus; Basuki, Hari Arbiantara; Kristianta, Franciscus Xaverius (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2022)
The development of technology and industry is currently being followed by increasing demand from the industry for mining or mineral materials, one of which is tin. Indonesia as the second largest tin producing country in the world plays a very important role in the development of technology and industry in the world. In Indonesia, tin mining is carried out by several companies, one of which is PT Timah (Persero) Tbk. This study aims to determine the effectiveness of the KIP 17 dredger system is 77% and the critical components obtained are the shaft and joint on the pump. The results of the analysis using Fishbone diagrams show that the quality of bolts and nuts and sealsused is not good. With the results of the study, it is recommended to increase personnel, especially in maintenance activities, and to improve the quality of nuts, bolts, and seals so as not to cause water to enter which can damage core components. Keywords—Mining, FMEA, Dredger